Dpep2 Emerging as a Modulator of Macrophage Inflammation Confers Protection Against CVB3-Induced Viral Myocarditis - Yang, Xiaoli; Yue, Yan; Xiong, Sidong (Frontiers in Cellular and Infection Microbiology, 2019)
Overwhelming cardiac inflammation has been reported to be the pathogenic mechanism of Coxsackievirus B3 (CVB3)-induced viral myocarditis (VMC), while the detailed molecular mechanisms remain unknown. Membrane-bound dipeptidases (MBD, also known as Dpep) have been shown to be involved in inflammatory diseases. However, the clear and direct evidence of their impacts on inflammation is still lacking. In this study, our results revealed that Dpep2 expression was remarkably increased during CVB3 infection, and primarily produced by the cardiac tissue-infiltrating macrophages instead of constitutive cardiomyocytes. Macrophages have been reported to play an important pathological role in driving viral myocarditis. Interestingly, macrophage-specific Dpep2 deletion robustly aggravated CVB3-induced cardiac inflammation, evidenced by augmented expression of TNF-α, IL-6 and MCP-1 in heart tissue. In addition, Dpep2-deficient bone-marrow derived macrophages (BMDMs) generated more TNF-α, IL-6 and MCP-1 after CVB3 stimulation compared with the control BMDMs. Moreover, this suppressive effect of Dpep2 on macrophages relied on its repression on NF-κB signaling pathway, but not on its conventional hydrolysate LTE4. Taken together, this study revealed that Dpep2 could protect against CVB3-induced viral myocarditis by acting as a suppressor of macrophage inflammation. Better understanding how macrophage Dpep2 dampened the cardiac inflammation would provide us with insights for the efficient control of CVB3-induced viral myocarditis.